Imaging Evaluation of the Axilla—A National Survey of Clinical Practice Among Radiologists. Issue 6 (27th October 2021) - Saksena, Mansi; Warner, Erica T; Chou, Shinn-Huey S; Lamb, Leslie; Narayan, Anand; Coopey, Suzanne; Lehman, Constance D
Abstract: Objective: To assess awareness and implementation of the American College of Surgeons Oncology Group Z0011 trial findings, approaches to axillary nodal imaging, and to identify differences in practice based on respondent characteristics. Methods: An online survey was distributed to members of the Society of Breast Imaging. Questions regarded demographics, evaluation approaches, and impact of the Z0011 trial. Poisson regression with robust standard errors to regression was used to generate multivariable-adjusted relative risks and 95% confidence intervals (CIs) for associations. Results: The response rate was 21.7% (430/2007). The majority (295/430, 68.6%) reported always performing axillary US in patients with a BI-RADS 4B, 4C, or 5 breast mass. Most respondents (299/430, 69.5%) were familiar with the findings of the Z0011 trial. Radiologists in academic practice were 0.67 (95% CI: 0.54–0.83) times less likely than private practice radiologists to perform axillary US in all masses and 1.31 (95% CI: 1.13–1.52) times more likely to be very familiar with the trial. Frequency of axillary US showed no association with time spent in breast imaging, years in practice, or presence of dedicated breast surgeons. Increased time in breast imaging and presence of dedicated breast surgeons was strongly associated with familiarity with the trial. No association was observed with years in practice. Most respondents (291/430, 67.7%) made little or no change to their practice based on trial findings. Conclusion: There is wide variability in approaches to axillary nodal evaluation, demonstrating a need for improved education and guidelines for axillary imaging in breast cancer patients.